Development of the constructionist concept in conjunction with the Bar model for a mathematics course - Chirarat Malai; Parichart Prasertsang (Gemilang Maju Publikasi Ilmiah (GMPI), 2023)
This research aims to 1. Find out the effectiveness of the plan to organize the mathematics course in the first grade according to the constructivist concept in conjunction with Bar Model. 2. Development of Mathematics Courses in Secondary Grade 1 in accordance with Constructivist Concepts in collaboration with Bar Model,3. Compare the students' ability to solve mathematical problems before the activity, including Nana, after the target group activity. Datong County Xiaojin Township Xiaojin Township No. 1 Middle School, the second semester of this year to study 2022, 4 academic years. People, in this study, are mobility studies, and information-gathering tools include plans to organize insight activities. By organizing 10 concept-based learning activities with the bar model, a way to measure the ability of mathematics to solve problems. Figure 5. The statistical range used to analyze the data includes the percentage, average, and deviation sections. The results of the study found that 1. Effectiveness of the plan to organize the mathematics course in the first grade according to the constructivist concept in conjunction with the bar model. Average evaluation result 4. 63 Most suitable level. 2. The results of the first grade mathematics course based on the constructivist concept and the bar model It has an average assessment result of 4.65. The most appropriate level. 3. Ability to solve math problems of students before the activity, the student passes the criteria. 70% of 2 students out of 4 students (50%) had an average of 66.25% and a standard deviation of 2.55%. 70% 4 people or 100% have an average of 78.33% and a standard deviation of 1.63%.